Evaluation of Purebred and Crossbred Chicken Under Backyard Condition - Radhakrishnan PM (Department of Poultry Science, College of Veterinary Science, 1981)
Data were collected from 45 farmers’ homesteads at Kanjikode, Palghat District using WLH, ALP, RIR and their possible two breed reciprocal crosses. Nine genetics group each having five replications of five birds each formed the experimental material. The birds were offered 50 per cent of daily mash requirement through balanced feed and the rest being through house hold waste. The livability among all genetic group was excellent. ALP x WLH cross was superior in age at sexual maturity and per cent egg production. WLH and RIR ranked next and RIR the last. The birds were able to maintain the production and body weight with 50 per cent of the ration, in backyard system. All the genetic groups except RIR showed profit. ALP x WLH appears as a promising bird for backyard system.